PEMBELAJARAN MENGUNGKAPKAN KEMBALI ISI BIOGRAFI B.J.HABIBIE DAN PENGARUHNYA PADA PEMBENTUKAN KARAKTER SISWA - Sukiman, Sukiman (Universitas Hamzanwadi, 2019)
This study aims to describe learning to re-express the biographical contents of characters. The study design uses descriptive qualitative. The data in this study are in the form of learning to reveal the biographical contents of the characters by students and student participation as well as the ability of students to express the biographical contents of the characters. Biographical texts used in learning, namely: 1) biographical texts that have character, 2) biographical texts that have religious value, 3) biographical texts that have services / works, and 4) biographical texts whose field of expertise is able to provide motivation for students. From some of these criteria, then in this study the biographical text used, namely: B.J. biography text Habibie, Ardian Syaf, and George Saa. Then, based on the results of the data analysis, several character values from the three figures were obtained, such as: firm, determined, hard working, independent, disciplined, fond of reading, responsibility, creative, curiosity, appreciating achievement.